Flowering Plants : Asteraceae, Part 1 - Mohlenbrock, Robert H., 1931- (Book collections on Project MUSE., 2015)
This, the first of three volumes on the aster family planned for the Illustrated Flora of Illinois series, recognizes 388 species in 119 genera, as well as 20 hybrids and 73 lesser taxa. In Asteraceae, Part 1, author Robert Mohlenbrock presents new and historic information in a clear and easy-to-read style. The volume provides an easy-to-use key to the genera and species and a complete description and nomenclatural and habitat notes for each plant, including its usefulness, if applicable. New nomenclatural combinations are shown for several species. The precise illustrations and detailed info.